The identification of the methylation patterns of tomato curly stunt virus in resistant and susceptible tomato lines - Mulaudzi, Precious Earldom; Koorsen, Gerrit; Mwaba, Imanu; Mahomed, Nasima Banu; Allie, Farhahna (Frontiers in Plant Science, 2023)
Tomato curly stunt virus (ToCSV) is a monopartite begomovirus infecting tomatoes in South Africa, with sequence similarity to tomato yellow leaf curl virus (TYLCV). While there are numerous reports on the mechanism of TYLCV resistance in tomato, the underlying mechanisms in the tomato-ToCSV pathosystem is still relatively unknown. The main aim of this study was to investigate and compare the global methylation profile of ToCSV in two near-isogenic tomato lines, one with a tolerant phenotype (T, NIL396) and one with a susceptible phenotype (S, NIL395). Bisulfite conversion and PCR amplification, coupled with a next-generation sequencing approach, were used to elucidate the global pattern of methylation of ToCSV cytosine residues in T and S leave tissue at 35 days post-infection (dpi). The extent of methylation was more pronounced in tolerant plants compared to susceptible plants in all sequence (CG, CHG and CHH) contexts, however, the overall methylation levels were relatively low (<3%). Notably, a significant interaction (p < 0.05) was observed between the viral genomic region and susceptible vs. tolerant status for CG methylated regions where it was observed that the 3'IR CG methylation was significantly (p < 0.05) higher than CG methylation of other genomic regions in tolerant and susceptible plants. Additionally, statistically significant (EdgeR p < 0.05) differentially methylated cytosines were located primarily in the genomic regions V2/V1 and C4/C1 of ToCSV. The relative expression, using RT-qPCR, was also employed in order to quantify the expression of various key methylation-related genes, MET1, CMT2, KYP4/SUVH4, DML2, RDM1, AGO4 and AGO6 in T vs. S plants at 35dpi. The differential expression between T and S was significant for MET1, KYP4/SUVH4 and RDM1 at p<0.05 which further supports more pronounced methylation observed in ToCSV from T plants vs. S plants. While this study provides new insights into the differences in methylation profiles of ToCSV in S vs. T tomato plants, further research is required to link tolerance and susceptibility to ToCSV.